Principles of pavement engineering - Thom, Nick (ICE Publishing, 2013)
'Principles of Pavement Engineering' expands on the fundamental principles of pavement engineering, concentrating on an understanding of the behaviour of pavement materials and of the real meaning of tests carried out on those materials.